2016
DOI: 10.1016/j.jsxm.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Personality and Behavioral Mechanisms Defining Hypersexuality in Men Who Have Sex with Men

Abstract: Objective The purpose of this study was to investigate personality factors and behavioral mechanisms that are relevant to hypersexuality in men who have sex with men. Method A sample of 242 men who have sex with men were recruited from various sites in a moderate size mid-western city. Participants were assigned to hypersexuality or control group using a SCID-type interview. Self-report inventories were administered that measured the broad band personality constructs of positive emotionality, negative emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 53 publications
(73 reference statements)
4
26
0
Order By: Relevance
“…In the case of hypersexuality, research has shown that impulsivity is weakly or moderately associated with hypersexual behaviors, fantasies, and urges (Pachankis et al, 2014;Reid et al, 2014;Walton et al, 2017). However, comparisons of hypersexual and nonhypersexual individuals have not shown consistent results (Miner et al, 2016;Mulhauser et al, 2014). The results of the present study corroborate the findings of Pachankis et al (2014) and Reid et al (2014) because the associations between impulsivity and hypersexuality are positive and moderate, suggesting that impulsivity may contribute importantly to the development and maintenance of hypersexuality.…”
Section: The Role Of the Impulsivity And Compulsivity In Hypersexualisupporting
confidence: 71%
See 3 more Smart Citations
“…In the case of hypersexuality, research has shown that impulsivity is weakly or moderately associated with hypersexual behaviors, fantasies, and urges (Pachankis et al, 2014;Reid et al, 2014;Walton et al, 2017). However, comparisons of hypersexual and nonhypersexual individuals have not shown consistent results (Miner et al, 2016;Mulhauser et al, 2014). The results of the present study corroborate the findings of Pachankis et al (2014) and Reid et al (2014) because the associations between impulsivity and hypersexuality are positive and moderate, suggesting that impulsivity may contribute importantly to the development and maintenance of hypersexuality.…”
Section: The Role Of the Impulsivity And Compulsivity In Hypersexualisupporting
confidence: 71%
“…However, when hypersexual and nonhypersexual males were compared regarding their level of impulsivity, only a trend toward significance was found in relation to impulsivity (Mulhauser et al, 2014). In another study comparing impulsivity between hypersexual gay men and nonhypersexual gay men (Miner et al, 2016), only one significant difference was observed. Hypersexual gay men showed elevated levels of nonplanning impulsivity compared to non-hypersexual gay men.…”
Section: Impulsivity Hypersexuality and Pornography Consumptionmentioning
confidence: 88%
See 2 more Smart Citations
“…Higher levels of sexual excitation have repeatedly been observed in individuals with out-of-control sexual behaviour (Bancroft and Vukadinovic, 2004 ; Janssen and Bancroft, 2007 ; Winters et al, 2010 ; Rettenberger et al, 2016 ). On the other hand, sexual inhibition has shown to be weakly or not related to hypersexual behaviours (Miner et al, 2016 ; Rettenberger et al, 2016 ), but has shown to be lower in individuals who engage more in risky sexual practices (Bancroft et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%